Structal and Optical Properties Algaas Nanowires Grown by Mbe on Si(111) Substrate. (December 2019) - Vershinin, A V; Shtrom, I V; Kotlyar, K P; Filosofov, N G; Serov, A Yu; Samsonenko, Yu B; Ilkiev, I V; Reznik, R R; Cirlin, G E
Abstract: In this work, we present the results of photoluminescence measurements of wurtzite AlGaAs nanowires, coupled with the transmission electron microscopy structural analysis. AlGaAs NWs were grown by molecular beam epitaxy under the nominal aluminum content of 0.3 - 0.8. The results of TEM measurements demonstrated wurtzite crystal structure of AlGaAs nanowires.